Calcium oxide-enhanced phosphorus recycling using sewage sludge degradative solvent extraction technology. (15th August 2022) - Yang, Shou-meng; Zhang, Li-hui; Duan, Feng
Highlights: Sewage sludge was treated using degradative solvent extraction technology. Effective separation of organic and phosphorus enrichment was both obtained. Soluble with high volatile and near-zero ash has high-value utilization potential. The content of bioavailable phosphorus in sludge can be increased by adding CaO. Abstract: This study proposes a novel calcium oxide-enhanced phosphorus recycling technique using sewage sludge degradative solvent extraction. We investigated the effects of extraction parameters such as the temperature, holding time, and sludge/extractant ratio on the soluble yield and phosphorus distribution in the residue. The enhancement mechanisms of the apatite phosphorus (AP) content after adding CaO for degradative solvent extraction were also studied. The results showed that the effective separation of organic matter and phosphorus enrichment were simultaneously achieved. An increase in the extraction factors promoted the extraction of organic matter. The peak soluble yield is 13.30 g/100 gSS which was obtained at extraction temperature of 300 °C, holding time of 60 min and sludge/extractant ratio of 100/300 g/mL. The soluble matter with high amounts of volatile matter and near-zero ash content has high-value utilization potential. After the degradative solvent extraction, almost all P in the sewage sludge was enriched in the residue. The organic phosphorus (OP) in the residue almost disappeared, and the proportion of non-apatite inorganic phosphorus (NAIP) increased. As the amount of added CaO increased from 0 to 10 g, the proportions of AP in TP increased from 36.55 to 80.15%, while that of NAIP decreased from 61.93 to 14.77%. The transformation of P from OP to the inorganic species during extraction was promoted by the addition of CaO, particularly for the formation of hydroxylapatite.